THE VALUE OF XANTHINE IN CHRONIC HEART FAILURE - Ergasheva Ma’mura Toshtemirovna; Khusainova Munira Alisherovna; Yarmatov Suvon Totlibayevich; Boyqobilov Suhrob Duskobilovich (Journals Park Publishing, 2022)
The article presents the data of a study on the study of xanthine metabolism disorders in patients with chronic heart failure (CHF), depending on the presence or absence of concomitant chronic kidney disease (CKD) at different stages of the disease. There was a significant increase in the activity of xanthine oxidase in patients with chronic heart failure with concomitant chronic kidney disease, which proves a change in the metabolism of this category of patients in the direction of the oxidase pathway of uric acid formation. The negative effect of xanthine metabolism disorders on the clinical course of CHF and the progression of the functional class of heart failure was demonstrated. At the same time, in patients with CHF with CKD, the progression of the functional class and a decrease in the left ventricular ejection fraction is associated with an increase in xanthine oxidase activity, while in patients with CHF without concomitant CKD – only with an increase in serum uric acid levels. The results also indicate an important role of the xanthine oxidase system in the deterioration of kidney function.
Keywords: xanthine oxidase; chronic heart failure; chronic kidney disease